Project Description - Dhanabalan, Manesa (SOURCE: Sheridan Institutional Repository, 2021)
The Blurred Lines of Racism is a multimedia website focusing on an issue that is both polarizing and highly misunderstood. Although Canada is seen as being very tolerant, hate crimes here rose sharply in 2017–up 47% over the previous year. Our First Nations’ communities face serious issues with water quality and access to care, and multiple police forces have been censured for racist policies. This project examines the psychology of racism and how racism is institutionalized in our health care, judicial, and education systems. It identifies where racism comes from, where it still lives, and sheds light on debates surrounding flashpoints such as the use of the “N” word, hijabs, Islamaphobia, Holocaust denial, white privilege, hi-tech racism, and cultural appropriation. As Canada is closely tied to the U.S. by location, media systems, and some aspects of culture, we also touch on issues south of our border. Data housed within the site come from multiple sources and modes of delivery, including on-camera interviews with subject experts, people who have faced racial discrimination/bias, and even personal stories from students who developed the site; for example, in a short podcast, our project coordinator shares how she was told by relatives she wasn’t as “pretty” as her sisters because her skin was too dark. We also use graphics to better explain statistics, unpack and link to a variety of academic and journalistic articles and videos related to racism, and use social media comments to capture current discourse. The goal of the project was not to give concrete answers to some really complicated questions, but to help people understand what it feels like when you are the person who’s the target of racist behaviour and how racist behaviour emerges. We see it as an important resource to both shed light on the full impact of racism and to provide access to ideas on how to effect positive change.